PENGENALAN SASTRA ANAK UNTUK MENINGKATKAN LITERASI BACA TULIS ANAK - Intanrawit Sapanti; Tristanti Apriyani; Resneri Daulay (ASOSIASI IDEBAHASA KEPRI, 2021)
The low literacy of children in Indonesia is quite alarming because it can affect the competence of critical thinking, creativity, communication and collaboration that Indonesian children should have. One of the effective ways to ensure that the 4C competency mastery is achieved is by improving and fostering the reading literacy skills of Indonesian children. The purpose of this community service activity is to introduce children literature to children with the aim of increasing their interest in reading and literacy from an early age. It is hoped that in the future, by knowing and reading various literary works, moral values and the cultivation of good character can be given to children. By carrying out this training, it is hoped that students can produce a simple children's work / story in the form of an anthology work. The method of implementing this activity is divided into three stages, namely; the preparation stage, the implementation stage, and the final reporting stage. This activity involved two students, namely Rida Alifia (Indonesian Literature Department) and Andini Mandala Putri (English Literature Department). The community service activity partner is SD Negeri Gentan, and community service activity is conducted in SD Negeri Gentan on 21 November 2020, 28 November 2020, 5 December 2020 and 12 December 2020 through zoom meeting online. This activity was attended by 47 students of SD Negeri Gentan and was very well appreciated by the students and teachers. Students can listen well to 4 children's stories submitted by team members. They are able to answer well and retell the contents of the children's stories. The targets and outputs of this community service activity are scientific publication manuscripts published in journals, articles published in print media, activity videos, and IPR certificates. The output target that has been achieved is the production of children's story videos that have been uploaded on the YouTube channel of the Indonesian Literature Study Program, while other output targets such as publication texts and IPR certificates are in process. Key words: children literature, literacy, character development